Effect of Replacing Wheat Bran with Acacia seyal Pods on the Performance of Tigray Highland Sheep - Weldegebriel, Berhe; Yadav, K. R. (Indian Journal of Animal Nutrition, 2017)
Twenty Tigray Highland sheep were divided into 5 groups of 5 animals each using randamised block design. The animals were fed ad lib. grass hay (basal ration), basal ration + 306 g of Acacia seyal pods (100%), basal ration + 204 g (66.7%) Acacia seyal pods and 102 g (33.3%) wheat bran, basal ration + 102 g (33.3%) of Acacia pods and 204 g (66.7%) wheat bran, basal ration + 306 g (100%) wheat bran in groups T1, T2, T3, T4 and T5, respectively during a feeding trial of 90 days. Carcass evaluation was done at the end of the digestibility trial. Total DM, OM and CP intakes were higher (P<0.001) in supplemented groups than the control group (Grass hay). The highest daily body weight gain was recorded in animals fed Acacia pods (group T2; 51.1 g/d) and the lowest (28.4 g/d) in group T1. Significant differences were noticed between the treatments in rib eye area muscle. Dry matter intake was positively (P<0.01) correlated with the intakes of OM, CP, NDF and ADF. The dressing percentage on slaughter weight and empty body weights basis and rib eye area were significantly (P<0.01) higher in supplemented groups than the control one. No significant differences were observed in edible and non-edible offal’s and total edible and non-edible percentages. Partial budget analysis showed that the highest total income and economical profitability was observed in groups fed Acacia seyal pods. It was concluded that the performance of Tigray Highland sheep could be improved when the rations were supplemented with 100% (306 g) Acacia seyal pods with ad lib. grass hay.